The Influence of Live Streaming Shopping on Purchase Decisions through Customer Engagement on Instagram Social Media - Galih Ginanjar Saputra; Fadhilah Fadhilah (Budapest International Research and Critics University, 2022)
Various digital platforms continue to innovate as a form of solution offered to business people. Live Streaming Shopping is now a new trend in marketing strategies using online platforms. The live feature on Instagram social media allows business people to offer products in real time, provide detailed information about products, answer questions from potential buyers or conduct other interactions with potential buyers. This study aims to analyze the influence of live streaming shopping on Instagram social media on customer engagement, to analyze the influence of customer engagement on purchasing decisions, and to analyze the influence of live streaming shopping on purchasing decisions through customer engagement on Instagram social media. This research was conducted on respondents who have followed and made purchases through live streaming shopping on Instagram social media. This type of research is carried out using explanatory research, with quantitative methods. Furthermore, the data were analyzed using Path Analysis technique or path analysis to determine the direct and indirect effects of the variables studied. This study provides several theoretical and managerial implications for business actors.